White pea beans: Ethiopia's latest cash crop - Birachi, Eliud Abucheli (International Center for Tropical Agriculture, 2011)
International market opportunities for Ethiopian white pea beans are soaring sky high. Ever since beans were included in Ethiopia's Commodity Exchange (ECX), world markets for white pea beans have grown significantly. The ECX is a unique partnership of market actors who promote the country's agricultural products. The bulk of who include traders, cooperative unions, and the government. As a trade organization, it serves markets in Europe, Middle East, southern and northern Africa, India, and Pakistan. The International Center for Tropical Agriculture (CIAT, its Spanish acronym) is a research organization based in Colombia that facilitates the work of the Pan-Africa Bean Research Alliance (PABRA) in 28 countries of sub-Saharan Africa. The CIAT-PABRA collaboration, working through the Ethiopian Institute of Agricultural Research (EIAR), has been an important part of Ethiopia's development efforts since 2004.